Understanding innate immunity and inflammation in acne: implications for management. (June 2015) - Dreno, B.; Gollnick, H.P.M.; Kang, S.; Thiboutot, D.; Bettoli, V.; Torres, V.; Leyden, J.; ,
Abstract: Acne has long been understood to have a complex physiological basis involving several main factors: hormonally‐stimulated sebum production, abnormal keratinization of the pilosebaceous duct, and an inflammatory immune response to Propionibacterium acnes . Recent studies at the molecular and cellular level have begun clarifying how all of these factors interact, and the role of the innate immune system is better appreciated. Inflammation has been demonstrated in all acne lesions ‐ the preclinical microcomedo, comedones, inflammatory lesions, 'post‐inflammatory' erythema or hyperpigmentation, and scarring. Inflammation localized to the pilosebaceous unit can be considered the defining feature of acne and should be addressed via multiple therapeutic pathways. Clinicians tend to think oral antibiotics should be used to 'calm' inflammatory acne, but there is good evidence showing that topical retinoids also have anti‐inflammatory properties as a class effect. For best therapeutic outcomes, most patients with acne should be treated first line with a topical retinoid plus an antimicrobial agent, as has been demonstrated in thousands of patients involved in clinical trials and recommended by the Global Alliance to Improve Outcomes in Acne for more than a decade. Moving away from reliance on antibiotic therapy for acne is particularly important in an era of worsening antimicrobial resistance and worldwide calls to reduce antibiotic use. Improved understanding about the role of P. acnes and the innate immune system in acne should help clinicians in designing efficacious treatment strategies.